Audit Operasional: Solusi Atas Biaya DeadStock - Christian - Linardo; Carmel - Meiden; Eddy - Winarso (Jurnal Akuntansi)
In manufacturing company, effectiveness and efficiency of inventory control can affect the corporate earnings significantly. According to the observation, the author found a large number of dead stock at PT X. Therefore, the author decided to carry out an operational audit of inventory control in the company.The audit steps are preliminary audit, test of management control, audit in depth, reporting, and follow up. The methods used by the author to collect the data are observation for six months, focus group discussion with management, internal control questionnaires for three middle managers, and data documentation.According to the analysis’ result, author found large number of dead stock. The accumulation of dead stock disturbed corporate cash flow so that the company had to make loans to third parties and company had to pay interest charges. In addition, there’s also the exhibition cost. The accumulated expense of dead stock for 2017 was recorded at IDR 522,130,391.43.Several of main causes of the dead stock are the lack of market research, lach of control by stock keeper, and other factors. The author suggested internal improvement such as the determination of clear boundaries for inventories, and external improvement such as doing market research more often.